An exploratory study on the progress of "Habitat-Hyderabad" - Yogesh, Kumar; Kaji, Hideki; Kammeier, Hans Detlef; Apichat Wongkaew; Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1980)
The research done here presents a comprehensive picture of how the Habitat Hyderabad project came into existence. It analytically describes how a similar project can be made applicable in other cities of India where slums constitute 20 to 35 per cent of the total urban population. In Hyderabad alone, it was estimated that every sixth person living in the city was a slum dweller. The research is important primarily because it holds true that a people's centred approach can bring desirable results in changing the slum community through self-help and self-organizing efforts. This means that to organize people trained social workers and planners are required to read people's sentiments and needs, and to act on them. In doing so, consistent efforts are required by the government, planners, social workers, banks and people at large. To prove the project replicable, the author has drawn a methodology chart in the concluding chapter and is confident that, in spite of all the difficulties at implementing level, the project is more meaningful in smaller cities where there are fewer measurable disparities among people and therefore fewer local problems. After all, housing is a local issue.
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1980
Keywords: Public housing -- India -- Hyderabad